BREXIT RELATED UNCERTAINTY FOR UNITED KINGDOM ECONOMY - Wielechowski, Michał; Czech, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2016)
The aim of research is to present economic and financial uncertainty related to Britain's exit from the European Union (EU). Paper discusses and analyses the pre-referendum characteristics of Brexit, the problem of growing uncertainty and its impact on British financial markets and the economy of the United Kingdom (UK), and possible scenarios of future UK-EU relationship. Post-referendum Economic Policy Uncertainty Index (EPU) levels indicate growing uncertainty in British economy. The most evident pro-Brexit voting effect was a substantial depreciation of British pound (GBP). Economic forecasts indicate negative impact of Britain's withdrawing from the EU on gross domestic product (GDP) growth rate in 2016-2020. The most likely scenario for post-Brexit UK-EU relationship is going to be a "hard Brexit".